FUZZY LOGIC IN AGRICULTURE: BRIEF HISTORY - Godinho, Emmanuel Zullo [UNESP]; Gasparotto, Helio Vagner [UNESP]; Caneppele, Fernando de Lima (Inst Fed Education, Science & Technology Of Goias, Campus Inhumas, 2022)
The objective of this article was through a systematic bibliographic review to verify the answer to the question How is the state of historical knowledge about the application of Fuzzy logic in agriculture registered?. The systematic bibliographic review is a scientific method for searching and analyzing articles from a specific area of science. It is widely used in research in medicine, psychology and agriculture and related areas, where there are large masses of data and sources of information. Due to relevance, the Scopus (R) ELSEVIER database was selected. It was observed that the words Agriculture and Logic fuzzy were used in the research as one-dimensional strings. After applying the filters, 42 articles were selected, which had a survey of the content to verify the results. After this survey, the articles were grouped by the themes bioenergy, soil, irrigation and drainage, digital humanities, sustainability, technology integrated to the internet and combinations between the themes. It was concluded that the Fuzzy Logic and its applicability in agriculture is widespread in the world and that it brought technological advances capable of collaborating to solve complex agricultural problems of great scope producer in some handling with animals and/or with the cultural treatments in the crops, thus consolidating the importance of interdisciplinary technique and capable of collaborating with the results of the producer rural.
Keywords: agriculture; fuzzy logic; digital humanities